Review—Ink-Jet Printed Wireless Liquid and Gas Sensors for IoT, SmartAg and Smart City Applications. Issue 10 (1st January 2018) - Alreshaid, A. T.; Hester, J. G.; Su, W.; Fang, Y.; Tentzeris, M. M.
Abstract : The manuscript explores the process of integrating chemical and substance (liquid or gas) detecting sensors into the Internet of Things (IoT). Focusing on recently developed sensors that are integrated into wireless platforms, a microfluidic sensor and its mechanism to detect different types of liquids are illustrated before examining gas sensors that can detect the presence of targeted gases in very small amounts; 2.5 ppm (parts per million) for dimethyl methyl phosphonate (DMMP), 2.0 ppm for diethyl ethyl phosphonate (DEEP) and 10 ppm for ammonia (NH3 ). Finally, four Radio Frequency Identification platforms embedded with sensors are mentioned showing how they transmit info through frequency tuning.